Stability of vertical dimension following total arch intrusion - Dong-Ok Kang; Hyung-Seog Yu; Sung-Hwan Choi; Seong-Taek Kim; Hwi-Dong Jung; Kee-Joon Lee (BMC, 2023)
Abstract Background The purpose of this study is to evaluate stability of vertical dimension following total arch intrusion using miniscrews by measuring the change during treatment and relapse amount after more than one year of retention. Methods Thirty patients (6 men, 24 women) were included in this study. Lateral cephalographs were taken with conventional radiography at the start of treatment (T0), after treatment (T1), and at least one year after treatment (T2). The evaluation was performed by measuring changes of selected parameters during treatment and the extent of relapse after more than one year. Results During total arch intrusion treatment (T1-T0), anterior and posterior teeth intruded significantly. The mean vertical distance between the maxillary posterior teeth and palatal plane was reduced by 2.30 mm (P < 0.001). The mean vertical distance between the maxillary anterior teeth and palatal plane was reduced by 2.04 mm (P < 0.001). The anterior facial height was also reduced by 2.70 mm (P < 0.001). During retention period (T2-T1), the vertical distance between the maxillary anterior teeth and the palatal plane significantly increased by 0.92 mm (P < 0.001). The anterior facial height increased by 0.81 mm (P < 0.01). Conclusions Anterior facial height significantly decreases after treatment. During retention period, relapse of AFH and maxillary anterior teeth observed. There was no correlation between initial amount of AFH, mandibular plane angle, or SNPog and posttreatment AFH relapse. However, there was a significant correlation between the amount of intrusion of anterior and posterior teeth achieved by the treatment and the extent of relapse.